Synchrotron 3D SAXS analysis of bone nanostructure. Issue 2 (April 2012) - Seidel, Robin; Gourrier, Aurelien; Kerschnitzki, Michael; Burghammer, Manfred; Fratzl, Peter; Gupta, Himadri Shikhar; Wagermaier, Wolfgang
Abstract : The complex structure of bone requires a structural description of the material at different hierarchical levels. At the micrometer level, collagen fibril orientation and osteocyte network architecture can be described by different light microscopy methods. However, further investigation of the nanostructure of bone requires high-resolution techniques such as electron microscopy as well as x-ray scattering methods. The basic building blocks at the nanometer level are organic type I collagen fibrils reinforced by nanoparticles of carbonated apatite mineral. Most commonly, these fibrils aggregate into lamellae of about 5 µm width, in both compact and spongy bone. The architecture of the mineral platelets and the collagen fibrils influences the mechanical properties. Models of twisted and rotated plywood motifs have been proposed, although detailed quantitative characterization at length scales comparable to typical tissue unit sizes are still lacking. Here, we describe a scanning small-angle x-ray scattering (SAXS) method to reconstruct the variation of the three-dimensional habit of mineral platelets within osteonal bone. We find that the platelets change their orientation at micrometer resolution and are organized structurally by a repeating unit of about 5 µm, which is in agreement with previous wide-angle x-ray diffraction microtexture measurements. At the spatial resolution of the microbeam used (1 µm), we observe fiber geometry. The presented SAXS reconstruction technique could also be applied to the analysis of nanoparticle orientation in highly textured biomaterials.